Securing Cloud Storage Using Aes Based On Geo-Key Method - Nur Syafiqah binti Mohd Shamsuddin
Anything connected to the internet is exposed to cyber risks including the risk of a personal data breach in cloud storage. The use of the internet has risen significantly nationwide during the Covid-19 pandemic resulting in a huge number of cyber incidents being reported. According to the Internet Users Survey (IUS), 2020 report by the Malaysian Communications and Multimedia Commission (MCMC), the percentage of internet users in 2020 grew by 1.3% from 87.4% in 2018 to 88.7% in 2020 while a total of 8,669 cybersecurity incidents were reported to the Cyber Security Malaysia in 2021. As a result of the increasing number of internet users, there are three major data security issues identified that need to be enhanced which are (i) secure file storage, (ii) vulnerable encryption key, and (iii) lack of remote access restriction at cloud storage. One of the strongest options to provide security for file protection in the storage is by implementing a cryptographic method that includes encryption and decryption process. However, strong encryption method such as the AES method is still available to be attacked if the encryption key is vulnerable. Adaptation to a post-pandemic environment by working remotely from the physical office has also attracted unauthorized remote access to files in cloud storage due to a lack of location-based access restrictions. Therefore, to improve the security of accessibility files in storage, this research aims to develop an enhanced cryptographic method by implementing location information to generate the encryption key using the AES method. The enhanced AES method is developed by using the combination of longitude and latitude coordinates, user password, and device MAC address to generate the encryption key known as geo-key. Then, it is evaluated to verify its performance by conducting a time performance comparison between the existing method and the enhanced AES method using a variety of format types as the data set. The result shows that the enhanced AES method takes 2.73% longer time to execute than the existing AES method takes due to the additional combination of key parameters to generate the geo-key while the existing AES method only required a single parameter to generate the key encryption which is the user password. Next, the enhanced AES method is evaluated by validating file decryption successfulness at a different location where it has shown that only files located at an intended location can be decrypted subject to their toleration range of distance. The other testing has been conducted to evaluate the integrity of decrypted files which showing all files that have been decrypted are having the same hash value as the original file’s hash. The results from this third evaluation have proved that the enhanced AES geo-key method keeps the integrity of the original data without any unintended modification and corruption. The enhanced AES method has a significant contribution to protect files in storage if the file has been stolen in the situation of security data breach incident as the encrypted file could never be accessed by an unauthorized owner and only be decrypted inside the intended range of location. This research also aligned with one of the pillar strategies in Malaysia Cyber Security Strategy (MCSS) to establish data leakage protection mechanisms in organization management and business operation.